Crime Motivation of Recidivist Inmates in the Class 1 State Detention Center (Rutan) Surakarta - Panggayuh, Dimas Galih; Fadloli, Alfiandra Daffa Nur; Meilina, Ragil Tri; Lestari, Rini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Many problems arise in the detention center related to the coaching of Correctional Inmates. Even though some inmates are recidivists, they even move to different detention centers. In this case, the inmates certainly have their motivation in committing the crime so they become a recidivist. The purpose of this research was to describe recidivist inmates' motivation in committing their crimes. This research used the qualitative method by doing interviews and observations to collect the data. The data were analyzed through a descriptive narrative. The subjects were 5 inmates in the Class I State Detention Center (Rutan) Surakarta who committed repeated crimes in various cases. The result of this research shows the motivation of inmates in recidivism is influenced by economic factors, environmental factors, psychological factors, the influence of others, opportunities, and habits to commit crimes. To reduce recidivists from committing crimes, it is necessary to pay attention to the factors that trigger these crimes.